"Transcriptomics": molecular diagnosis of inborn errors of metabolism via RNA‐sequencing. Issue 3 (25th January 2018) - Kremer, Laura S.; Wortmann, Saskia B.; Prokisch, Holger
Abstract: Exome wide sequencing techniques have revolutionized molecular diagnostics in patients with suspected inborn errors of metabolism or neuromuscular disorders. However, the diagnostic yield of 25–60% still leaves a large fraction of individuals without a diagnosis. This indicates a causative role for non‐exonic regulatory variants not covered by whole exome sequencing. Here we review how systematic RNA‐sequencing analysis (RNA‐seq, "transcriptomics") lead to a molecular diagnosis in 10–35% of patients in whom whole exome sequencing failed to do so. Importantly, RNA‐sequencing based discoveries cannot only guide molecular diagnosis but might also unravel therapeutic intervention points such as antisense oligonucleotide treatment for splicing defects as recently reported for spinal muscular atrophy.